Cooperative survival principles for underground flooding: Vitae System based multi-agent simulation. (15th October 2017) - Higo, Eishiro; Okada, Norio; Hipel, Keith W.; Fang, Liping
Highlights: Evacuation and rescue principles under life-threatening situations are clarified. A multi-agent simulation approach based on the Vitae System model is presented. A person's ability is characterized by survivability, vitality, and conviviality. Three strategies for the evacuation and rescue processes are simulated & compared. The results show that even people at risk (evacuees) can assist one another. Abstract: Evacuation and rescue principles under life-threatening situations are clarified using a simulation model designed with a Vitae System-based agent. The Vitae System model identifies an individual's ability to maintain his or her life under life-threatening situations as characterized by three functions: survivability, vitality, and conviviality. This simulation model forms a basis for analyzing rescue strategies. As an illustration, these three functions are specifically defined to operationalize the Vitae System conceptual model employing an underground inundation case study in which people must be evacuated. Three strategies for the evacuation and rescue processes under life-threatening flooding are simulated and compared. The results show that even people at risk (evacuees) can assist one another if there are sufficient and appropriate strategies and equipment for survival. In addition to the current mitigation plan, the suggested preparations for an extreme disaster provide another type of safety net for saving human life.